Comparative Transcriptome Profiling of Cold Exposure and β3-AR Agonist CL316,243-Induced Browning of White Fat - Li, Yu; Ping, Xiaodan; Zhang, Yankang; Li, Guoqiang; Zhang, Ting; Chen, Geng; Ma, Xinran; Wang, Dongmei; Xu, Lingyan (Frontiers in Physiology, 2021)
Beige adipocytes are newly identified thermogenic-poised adipocytes that could be activated by cold or β3-adrenergic receptor (β3-AR) signaling and offer therapeutic potential for treating obesity and metabolic diseases. Here we applied RNA-sequencing analysis in beige fat of mice under cold exposure or β3-AR agonist CL316,243 (CL) treatment to provide a comparative and comprehensive analysis for the similarity and heterogeneity of these two stimulants. Importantly, via KEGG analysis, we found that cold and CL commonly induced oxidative phosphorylation. Meanwhile, cold increased glycerolipid and amino acids metabolism while CL treatment triggered a broader spectrum of metabolic responses including carbohydrate metabolism. Besides, cold or CL treatment featured greater heterogeneity in down-regulated gene programs. Of note, the top changed genes in each category were confirmed by qPCR analysis. Overall, our analysis provided a better understanding of heterogeneity of differential models for beige adipocytes activation and possible clue for optimizing β3-AR agonists in future.